Adhesive sheet

The adhesive sheet, formulated with a specific combination of components and controlled mass ratios, addresses the issues of excessive hardness and air bubble formation in adhesive sheets used in display devices and touch panels, achieving stable stress relaxation and curability under different UV light sources.

JP7666262B2Active Publication Date: 2025-04-22OJI HLDG CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2021153667
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-09-21
Publication Date
2025-04-22
Estimated Expiration
2041-09-21

AI Technical Summary

Technical Problem

Adhesive sheets used in display devices and touch panels face issues with excessive hardness when exposed to ultraviolet rays after curing, leading to reduced stress relaxation and the formation of air bubbles at the interface.

Method used

The adhesive sheet contains a specific combination of (meth)acrylic copolymer, a crosslinking agent with two or more acryloyl groups, a hydrogen-extracted photoinitiator, and a self-cleavable photoradical initiator, with controlled mass ratios to prevent excessive hardening and ensure stable curability under different UV light sources.

Benefits of technology

The adhesive sheet maintains excellent step followability and stress relaxation even after exposure to ultraviolet rays, with a small difference in curability between high-pressure mercury lamps and UV LED lamps, ensuring stable performance regardless of the lamp type used during post-curing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007666262000001
    Figure 0007666262000001
Patent Text Reader

Abstract

To provide an adhesive sheet that is prevented from becoming too hard even if the sheet is exposed to ultraviolet light after hardened, has excellent step followability even after ultraviolet light exposure.SOLUTION: An adhesive sheet of the present invention includes (meth)acrylic copolymer (A), cross-linking agent (B) having two or more acryloyl groups, hydrogen-abstraction type photoinitiator (C), and self-cleavage type photoradical initiator (D), where the cross-linking agent (B) is included by less than 5 pts.mass for 100 pts.mass of the (meth)acrylic copolymer (A), the hydrogen-abstraction type photoinitiator (C) is included by 0.3 ps.mass or less for 100 pts.mass of the (meth)acrylic copolymer (A), and the self-cleavage type photoradical initiator (D) is included by 0.2 pt.mass or more for 100 pts.mass of the (meth)acrylic copolymer (A). The adhesive sheet has a value of R=S(LED) / S(HTML) at 0.8 to 1.2.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a pressure-sensitive adhesive sheet. [Background technology]

[0002] Adhesive sheets are used, for example, for bonding members (adherends) together, and are widely used in various fields. In recent years, such adhesive sheets have also been used for display devices such as liquid crystal displays (LCDs) and input devices such as touch panels. By using an adhesive sheet to bond each member of an optical display constituting a display device or an input device, various devices can be manufactured easily and with high precision.

[0003] When an adhesive sheet is used for applications such as display devices or optical displays, the adhesive sheet is required to have the ability to bond and fix members (adhesiveness) and the ability to fill printing steps (step conformability). Furthermore, since these applications are usually used for a long period of time, the adhesive sheet is required to have the ability to stably maintain its adhesive force for a long period of time and to be less likely to peel off due to shrinkage of the adherend (i.e., stress relaxation). From this perspective, for example, Patent Document 1 proposes a technology that uses an adhesive sheet containing a (meth)acrylic acid ester copolymer, an acrylic crosslinking monomer, and a specific photopolymerization initiator to suppress the decrease in holding force over time and the generation of air bubbles at the interface. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2009-292986 A Summary of the Invention [Problem to be solved by the invention]

[0005] In the case where the adhesive sheet contains a photopolymerization initiator as in the technology disclosed in Patent Document 1, when ultraviolet light is applied to a laminate formed by bonding members (adherends) together with the adhesive sheet, further curing (post-curing) proceeds, and the members in the laminate are more firmly bonded together. However, since the hydrogen abstraction photopolymerization initiator remains in the adhesive sheet even after ultraviolet light irradiation, if the laminate is further exposed to ultraviolet light during use, the curing of the adhesive sheet proceeds and the adhesive sheet becomes too hard. As a result, the stress relaxation property is reduced, causing problems such as the generation of air bubbles at the interface between the adhesive sheet and the adherend.

[0006] In addition, because hydrogen abstraction photoinitiators (e.g., benzophenone-based) have a main absorption wavelength in the short wavelength region of 350 nm or less, there is the problem that the curing properties differ when cured with a high-pressure mercury or metal halide lamp that also emits light on the short wavelength side and when cured with a UV LED lamp that only emits wavelengths around 365 nm.

[0007] The present invention has been made in consideration of the above, and aims to provide an adhesive sheet and a laminate comprising the adhesive sheet, which has excellent conformability to unevenness, is prevented from becoming too hard even when exposed to ultraviolet light after curing, has excellent stress relaxation properties even after exposure to ultraviolet light, and has a small difference in curing properties between a high-pressure mercury lamp and a UV LED lamp. [Means for solving the problem]

[0008] As a result of intensive research into achieving the above-mentioned object, the inventors have found that the above-mentioned object can be achieved by containing a specific crosslinking agent (B) and a photopolymerization initiator in predetermined amounts, and have thus completed the present invention.

[0009] That is, the present invention includes, for example, the subject matter described in the following sections. Item 1 A (meth)acrylic copolymer (A), A crosslinking agent (B) having two or more acryloyl groups; A hydrogen abstraction type photoinitiator (C); Self-cleavable photoradical initiator (D) Including, The crosslinking agent (B) is contained in an amount of less than 5 parts by mass relative to 100 parts by mass of the (meth)acrylic copolymer (A); the hydrogen abstraction type photoinitiator (C) is contained in an amount of 0.3 parts by mass or less based on 100 parts by mass of the (meth)acrylic copolymer (A); The self-cleavage type photoradical initiator (D) is contained in an amount of 0.2 parts by mass or more per 100 parts by mass of the (meth)acrylic copolymer (A), The following formula (1) R=S(LED) / S(HTML) (1) (Here, S(HPML) is the illuminance of 160mW / cm2 for the adhesive sheet. 2 The accumulated light intensity is 3000mJ / cm using a high-pressure mercury lamp. 2 After irradiating the sample with light, the sample was pulled at a speed of 300 mm / min until the tensile elongation reached 500%. The stress value [N / mm 2 ], and S (LED) is the illuminance of 160mW / cm2 against the adhesive sheet. 2 And an LED lamp with a wavelength of 365 nm is used, with an integrated light output of 3000 mJ / cm 2 After irradiating the sample with light, the sample was pulled at a speed of 300 mm / min until the tensile elongation reached 500%. The stress value [N / mm 2 ]) The pressure-sensitive adhesive sheet has an R value of 0.8 to 1.2. Section 2 Item 2. The pressure-sensitive adhesive sheet according to item 1, wherein the (meth)acrylic copolymer (A) has a glass transition temperature of −50° C. to −40° C. and a mass average molecular weight of 250,000 to 450,000. Section 3 3. The pressure-sensitive adhesive sheet according to item 1 or 2, wherein the (meth)acrylic copolymer (A) does not contain an acryloyl group in its structural unit. Section 4 Item 4. The pressure-sensitive adhesive sheet according to any one of items 1 to 3, which does not contain a thermal crosslinking agent. Section 5 Item 5. A laminate comprising the pressure-sensitive adhesive sheet according to any one of items 1 to 4. Effect of the Invention

[0010] The pressure-sensitive adhesive sheet of the present invention has excellent conformability to unevenness, is prevented from becoming too hard even when exposed to ultraviolet light after curing, and has excellent stress relaxation properties even after exposure to ultraviolet light. Furthermore, the pressure-sensitive adhesive sheet of the present invention has a small difference in curability between a high-pressure mercury lamp and a UV LED lamp. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, embodiments of the present invention will be described in detail. In this specification, the expressions "containing" and "comprise" include the concepts of "containing", "comprises", "consists essentially of" and "consists only of".

[0012] In the numerical ranges described in stages in this specification, the upper or lower limit of a certain numerical range can be arbitrarily combined with the upper or lower limit of another numerical range. In the numerical ranges described in this specification, the upper or lower limit of the numerical range may be replaced with a value shown in an example or a value that can be unambiguously derived from an example. In addition, in this specification, a numerical value connected with "~" means a numerical range that includes the numerical values ​​before and after "~" as the lower and upper limits.

[0013] 1. Adhesive sheet The pressure-sensitive adhesive sheet of the present invention is A (meth)acrylic copolymer (A), A crosslinking agent (B) having two or more acryloyl groups; A hydrogen abstraction type photoinitiator (C); Self-cleavable photoradical initiator (D) At least

[0014] In the pressure-sensitive adhesive sheet of the present invention, the crosslinking agent (B) is contained in an amount of less than 5 parts by mass per 100 parts by mass of the (meth)acrylic copolymer (A), the hydrogen abstraction type photoinitiator (C) is contained in an amount of 0.3 parts by mass or less per 100 parts by mass of the (meth)acrylic copolymer (A), and the self-cleavage type photoradical initiator (D) is contained in an amount of 0.2 parts by mass or more per 100 parts by mass of the (meth)acrylic copolymer (A).

[0015] The pressure-sensitive adhesive sheet of the present invention is a polymerizable compound represented by the following formula (1): R=S(LED) / S(HTML) (1) The value of R expressed by the formula is 0.8 to 1.2. Here, S(HPML) is the illuminance of 160 mW / cm2 for the adhesive sheet. 2 The accumulated light intensity is 3000mJ / cm using a high-pressure mercury lamp. 2 After irradiating the sample with light, the sample was pulled at a speed of 300 mm / min until the tensile elongation reached 500%. The stress value [N / mm 2 S (LED) is a light source with an illuminance of 160mW / cm2 for adhesive sheets. 2 And an LED lamp with a wavelength of 365 nm is used, with an integrated light output of 3000 mJ / cm 2 After irradiating the sample with light, the sample was pulled at a speed of 300 mm / min until the tensile elongation reached 500%. The stress value [N / mm 2 ])

[0016] The pressure-sensitive adhesive sheet of the present invention has excellent conformability to unevenness, is prevented from becoming too hard even when exposed to ultraviolet light after curing, and has excellent stress relaxation properties even after exposure to ultraviolet light. Furthermore, the pressure-sensitive adhesive sheet of the present invention has a small difference in curability between a high-pressure mercury lamp and a UV LED lamp, so its performance is stable regardless of the type of lamp used for post-curing.

[0017] ((Meth)acrylic copolymer) The pressure-sensitive adhesive sheet of the present invention contains a (meth)acrylic copolymer (A) as a constituent component. The (meth)acrylic copolymer (A) is the main component of the pressure-sensitive adhesive sheet of the present invention, and is the so-called base polymer of the pressure-sensitive adhesive sheet.

[0018] The type of (meth)acrylic copolymer (A) is not particularly limited, and for example, a wide variety of (meth)acrylic copolymers used to form known pressure-sensitive adhesive sheets can be used.

[0019] The (meth)acrylic copolymer (A) may have, for example, a (meth)acrylic acid alkyl ester unit. In this specification, the term "unit" refers to a repeating structural unit (also referred to as a monomer unit) constituting a polymer. The (meth)acrylic acid alkyl ester unit is derived from a (meth)acrylic acid alkyl ester. Examples of the (meth)acrylic acid alkyl ester include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, t-butyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, n-nonyl (meth)acrylate, isononyl (meth)acrylate, n-decyl (meth)acrylate, isodecyl (meth)acrylate, n-undecyl (meth)acrylate, n-dodecyl (meth)acrylate, stearyl (meth)acrylate, methoxyethyl (meth)acrylate, ethoxyethyl (meth)acrylate, cyclohexyl (meth)acrylate, benzyl (meth)acrylate, and isobornyl (meth)acrylate. The (meth)acrylic acid alkyl ester units contained in the (meth)acrylic copolymer (A) may be of one type alone or in combination of two or more types.

[0020] Among the above-mentioned (meth)acrylic acid alkyl esters, at least one selected from the group consisting of methyl (meth)acrylate, n-butyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate is preferred because it increases adhesion.

[0021] The (meth)acrylic copolymer (A) may have other acrylic monomer units other than the (meth)acrylic acid alkyl ester units. Examples of the other acrylic monomer units include acrylic monomer units having a crosslinkable functional group, such as hydroxyl group-containing acrylic monomer units and carboxyl group-containing acrylic monomer units. The (meth)acrylic copolymer (A) may contain one type of these monomer units, or may contain two or more types.

[0022] The hydroxyl group-containing acrylic monomer unit is derived from a hydroxyl group-containing acrylic monomer. Examples of the hydroxyl group-containing acrylic monomer include hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and 2-hydroxypropyl (meth)acrylate, (meth)acrylic acids [(mono-, di-, or poly) alkylene glycols] such as mono(diethylene glycol) (meth)acrylate, and (meth)acrylic acid lactones such as monocaprolactone (meth)acrylate. Examples of the carboxyl group-containing acrylic monomer unit include acrylic acid and methacrylic acid.

[0023] When the (meth)acrylic copolymer (A) has other acrylic monomer units other than (meth)acrylic acid alkyl ester units, the content of the other acrylic monomer units is preferably 0.01 to 20 mass% relative to the total mass of the (meth)acrylic copolymer (A), and more preferably 0.5 to 10 mass%. In particular, the content of the acrylic monomer units having a crosslinkable functional group is preferably within the above range. If the content of the other acrylic monomer units is equal to or greater than the above lower limit, the cohesive strength can be sufficiently increased, and if it is equal to or less than the above upper limit, sufficient adhesive strength can be easily ensured.

[0024] The (meth)acrylic copolymer (A) preferably does not contain an acryloyl group in its structural units, which makes it easier to produce the (meth)acrylic copolymer (A).

[0025] The glass transition temperature (Tg) of the (meth)acrylic copolymer (A) is not particularly limited. For example, the glass transition temperature (Tg) of the (meth)acrylic copolymer (A) can be set to -50°C to -40°C. In this case, the step conformability of the adhesive sheet can be more effectively improved, the cohesive force of the adhesive sheet can be more improved, the durability and adhesiveness are excellent, and the handleability of the adhesive sheet can be improved, so that processing becomes easier. The glass transition temperature (Tg) of the (meth)acrylic copolymer (A) is preferably -49°C or higher, more preferably -48°C or higher, and preferably -41°C or lower, more preferably -42°C or lower.

[0026] The mass average molecular weight (Mw) of the (meth)acrylic copolymer (A) is not particularly limited. For example, the mass average molecular weight of the (meth)acrylic copolymer (A) can be 250,000 to 450,000. This allows for a trade-off between step conformability and durability. The mass average molecular weight (Mw) of the (meth)acrylic copolymer (A) is preferably 260,000 or more, more preferably 280,000 or more, even more preferably 300,000 or more, and is preferably 430,000 or less.

[0027] The (meth)acrylic copolymer (A) particularly preferably has a glass transition temperature of -50°C to -40°C and a mass average molecular weight of 250,000 to 450,000.

[0028] The mass average molecular weight of the (meth)acrylic copolymer (A) is a value measured by gel permeation chromatography (GPC) and calculated in terms of standard polystyrene. The measurement conditions for gel permeation chromatography (GPC) are as follows. Solvent: Tetrahydrofuran Column: Shodex KF801, KF803L, KF800L, KF800D (four columns made by Showa Denko Co., Ltd. were used in combination) Column temperature: 40℃ Sample concentration: 0.5% by mass Detector: RI-2031plus (JASCO) Pump: RI-2080plus (JASCO) Flow rate (flow rate): 0.8ml / min Injection volume: 10μl Calibration curve: A calibration curve using 10 samples of standard polystyrene (Shodex standard polystyrene, manufactured by Showa Denko) with Mw=1,320 to 2,500,000 was used.

[0029] The (meth)acrylic copolymer (A) can be produced, for example, by a known method, for example, by polymerization reaction of acrylic monomers. In this case, various polymerization methods can be adopted, for example, solution polymerization method, emulsion polymerization method, suspension polymerization method, etc. In addition, the (meth)acrylic copolymer (A) can be obtained from a commercial product, for example, OP-9200-1, OP-9200-23, OP-9200-3, OP-9200-4, OP-9200-5, OP-9200-7, etc. manufactured by Aica Kogyo Co., Ltd.

[0030] (Crosslinking agent (B)) The pressure-sensitive adhesive sheet of the present invention contains a crosslinking agent (B) having two or more acryloyl groups as a constituent. The crosslinking agent (B) having two or more acryloyl groups is a so-called polyfunctional monomer. The crosslinking agent (B) having two or more acryloyl groups is referred to as a unit "crosslinking agent (B)".

[0031] The type of crosslinking agent (B) is not particularly limited, and for example, known polymerizable monomers having two or more acryloyl groups can be widely applied. Examples of crosslinking agent (B) include ethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, 1,3-butylene glycol di(meth)acrylate, 1,4-butylene glycol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,6-hexanediol diacrylate, polybutylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, diacrylate of bisphenol A diglycidyl ether, trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, and other polyhydric alcohol (meth)acrylic acid esters, vinyl methacrylate, etc.

[0032] The crosslinking agent (B) can be produced by a known method, or can be obtained from a commercially available product, such as ATM-4PL or A-TMM-3L manufactured by Shin-Nakamura Chemical Co., Ltd., PET-30 manufactured by Nippon Kayaku Co., Ltd., or Viscoat #230 manufactured by Osaka Organic Chemical Industry Co., Ltd.

[0033] (Hydrogen abstraction photoinitiator (C)) The pressure-sensitive adhesive sheet of the present invention contains a hydrogen abstraction type photoinitiator (C) as a constituent. The hydrogen abstraction type photopolymerization initiator (C) is a photopolymerization initiator in which an initiator photoexcited by irradiation with active energy rays and a hydrogen donor in the system form an exciplex, and the hydrogen of the hydrogen donor is transferred to promote polymerization. Thus, the hydrogen abstraction type photoinitiator (C) initiates a polymerization reaction of the crosslinking agent (B) and other polymerizable components that may be contained in the pressure-sensitive adhesive sheet of the present invention, and also acts on the (meth)acrylic copolymer (A) to form a crosslinked structure.

[0034] Here, the term "active energy rays" refers to electromagnetic waves or charged particle rays that have an energy quantum, and examples of such rays include ultraviolet rays, electron beams, visible light, X-rays, ion beams, etc. Among these, from the viewpoint of versatility, ultraviolet rays or electron beams are preferred, and ultraviolet rays are particularly preferred.

[0035] The type of hydrogen abstraction type photoinitiator (C) is not particularly limited, and examples thereof include benzophenone, benzoylbenzoic acid, methyl benzoylbenzoate, 4-phenylbenzophenone, hydroxybenzophenone, 3,3'-dimethyl-4-methoxybenzophenone, 2,4,6-trimethylbenzophenone, 4-methylbenzophenone, thioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone, 2,4-dimethylthioxanthone, isopropylthioxanthone, camphorquinone, dibenzosuberone, 2-ethylanthraquinone, 3,3',4,4'-tetra(t-butylperoxycarbonyl)benzophenone, benzil, 9,10-phenanthrenequinone, etc. Among them, the hydrogen abstraction type photopolymerization initiator (C) is preferably a benzophenone-based photopolymerization initiator. Examples of the benzophenone-based photopolymerization initiator include benzophenone, 4-methylbenzophenone, and 2,4,6-trimethylbenzophenone.

[0036] The hydrogen abstraction type photopolymerization initiator (C) can be produced by a known method, or can be obtained from a commercially available product. Examples of commercially available products include TZT and MBF manufactured by IGM Resins, and "SPEED CURE MBP" (e.g., "4MBP") manufactured by Lambson.

[0037] (Self-cleavage type photoradical initiator (D)) The pressure-sensitive adhesive sheet of the present invention contains a self-cleavage type photoradical initiator (D) as a constituent component. The self-cleavage type photoradical initiator (D) initiates a polymerization reaction of the crosslinking agent (B) and other polymerizable components that may be contained in the pressure-sensitive adhesive sheet of the present invention when irradiated with active energy rays. The self-cleavage type photoradical initiator (D) is other than the hydrogen abstraction type photopolymerization initiator (C).

[0038] The type of the self-cleavage type photoradical initiator (D) is not particularly limited, and examples thereof include acetophenone-based initiators, benzoin ether-based initiators, hydroxyalkylphenone-based initiators, thioxanthone-based initiators, amine-based initiators, and acylphosphine oxide-based initiators.

[0039] Specific examples of acetophenone initiators include diethoxyacetophenone and benzyl dimethyl ketal. Specific examples of benzoin ether initiators include benzoin and benzoin methyl ether. Specific examples of hydroxyalkylphenone initiators include 1-hydroxy-cyclohexyl-phenyl-ketone. Specific examples of thioxanthone initiators include 2-isopropylthioxanthone and 2,4-dimethylthioxanthone. Specific examples of amine initiators include triethanolamine and ethyl 4-dimethylbenzoate. Specific examples of acylphosphine oxide initiators include phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide.

[0040] The self-cleavage type photoradical initiator (D) may have an absorption wavelength peak at, for example, a wavelength of 220 to 450 nm. In particular, it is preferable that the self-cleavage type photoradical initiator (D) has an absorption wavelength peak at 340 to 390 nm. When the absorption wavelength peak of the self-cleavage type photoradical initiator (D) is less than 340 nm, it is preferable to use an appropriate sensitizer.

[0041] The self-cleavage type photoradical initiator (D) can be produced by a known method, or can be obtained from a commercial product. Examples of commercial products include EsacureOne, Omnirad 184, Omnirad 819, Omnirad 1173, Omnirad 2959, Omnirad 127, Omnirad 907, Omnirad 369, Omnirad 379G, Omnirad TPO, Omnirad TPO H, Irgacure OXE01, Irgacure OXE02, etc., manufactured by IGM RESINS BV.

[0042] (Adhesive sheet) As described above, the pressure-sensitive adhesive sheet of the present invention contains the (meth)acrylic copolymer (A), the crosslinking agent (B), the hydrogen abstraction type photoinitiator (C), and the self-cleavage type photoradical initiator (D), and therefore can be post-cured. For example, by irradiating an active energy ray such as ultraviolet light to a laminate formed by bonding adherends together with a pressure-sensitive adhesive sheet, the post-curing proceeds and the adherends are more firmly bonded together.

[0043] The pressure-sensitive adhesive sheet of the present invention has a crosslinking agent (B) content of less than 5 parts by mass, a hydrogen abstraction type photoinitiator (C) content of 0.3 parts by mass or less, and a self-cleavage type photoradical initiator (D) content of 0.2 parts by mass or more, relative to 100 parts by mass of the (meth)acrylic copolymer (A). This prevents the pressure-sensitive adhesive sheet of the present invention from becoming too hard even when exposed to ultraviolet light after curing, and has excellent stress relaxation properties even after exposure to ultraviolet light. In addition, the difference in curability between a high-pressure mercury lamp and a UV LED lamp can be reduced. Therefore, the pressure-sensitive adhesive sheet of the present invention has stable performance regardless of the type of lamp used during post-curing.

[0044] When the content of the crosslinking agent (B) is 5 parts by mass or more relative to 100 parts by mass of the (meth)acrylic copolymer (A), the pressure-sensitive adhesive sheet after post-curing becomes too hard, resulting in insufficient stress relaxation properties and easy generation of bubbles. When the content of the hydrogen abstraction type photoinitiator (C) exceeds 0.3 parts by mass relative to 100 parts by mass of the (meth)acrylic copolymer (A), the pressure-sensitive adhesive sheet becomes too hard when exposed to ultraviolet light after curing, resulting in poor stress relaxation properties and easy generation of bubbles. Note that a pressure-sensitive adhesive sheet that does not contain the hydrogen abstraction type photoinitiator (C) is difficult to cure even by post-curing, resulting in poor stress relaxation properties and easy generation of bubbles. When the content of the self-cleavage type photoradical initiator (D) is less than 0.2 parts by mass relative to 100 parts by mass of the (meth)acrylic copolymer (A), the crosslinking agent (B) and the like contained in the pressure-sensitive adhesive sheet are not sufficiently cured, causing a decrease in adhesive strength and a small value of R.

[0045] The content of the crosslinking agent (B) is preferably 4.5 parts by mass or less, more preferably 4 parts by mass or less, and even more preferably 3.5 parts by mass or less, based on 100 parts by mass of the (meth)acrylic copolymer (A). The content of the crosslinking agent (B) is preferably 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, and even more preferably 1 part by mass or more, based on 100 parts by mass of the (meth)acrylic copolymer (A).

[0046] The content of the hydrogen abstraction type photoinitiator (C) is preferably 0.25 parts by mass or less, more preferably 0.2 parts by mass or less, relative to 100 parts by mass of the (meth)acrylic copolymer (A). The content of the hydrogen abstraction type photoinitiator (C) is preferably 0.01 parts by mass or more, more preferably 0.05 parts by mass or more, and even more preferably 0.1 parts by mass or more, relative to 100 parts by mass of the (meth)acrylic copolymer (A).

[0047] Since the pressure-sensitive adhesive sheet of the present invention contains a hydrogen abstraction type photoinitiator (C) in a predetermined amount or less, even if the pressure-sensitive adhesive sheet is exposed to ultraviolet light for a long time after post-curing, the excessive reaction of the hydrogen abstraction type photoinitiator is suppressed, and the pressure-sensitive adhesive sheet does not become too hard. As a result, the pressure-sensitive adhesive sheet of the present invention can significantly suppress the generation of bubbles due to a decrease in stress relaxation property.

[0048] The content of the self-cleavage type photoradical initiator (D) is preferably 0.25 parts by mass or more, more preferably 0.3 parts by mass or more, based on 100 parts by mass of the (meth)acrylic copolymer (A). The content of the self-cleavage type photoradical initiator (D) is preferably 1 part by mass or less, more preferably 0.8 parts by mass or less, based on 100 parts by mass of the (meth)acrylic copolymer (A).

[0049] The pressure-sensitive adhesive sheet of the present invention may contain other components in addition to the (meth)acrylic copolymer (A), the crosslinking agent (B), the hydrogen abstraction type photoinitiator (C) and the self-cleavage type photoradical initiator (D) to the extent that the effects of the present invention are not impaired.

[0050] For example, the pressure-sensitive adhesive sheet of the present invention may contain a monofunctional monomer. The monofunctional monomer is a monomer having one reactive double bond (particularly, one polymerizable double bond) in the molecule. Examples of the monofunctional monomer include a wide range of known monofunctional monomers contained in pressure-sensitive adhesive sheets, such as (meth)acrylic ester compounds, (meth)acrylamide compounds, and other vinyl compounds.

[0051] Examples of (meth)acrylic ester compounds include isobornyl acrylate, isostearyl acrylate, methyl methacrylate, ethyl methacrylate, butyl methacrylate, benzyl methacrylate, and (meth)acrylates having a cyclic ether structure of a 4- to 6-membered ring. Examples of (meth)acrylamide compounds include N-acryloyloxyethylhexahydrophthalimide, acrylamide, N,N-dimethylacrylamide, and N,N-diethylacrylamide. Other examples include acryloylmorpholine and vinylpyrrolidone.

[0052] When the pressure-sensitive adhesive sheet of the present invention contains a monofunctional monomer, the content thereof is not particularly limited, and for example, the monofunctional monomer is preferably contained in an amount of 30 parts by mass or less, more preferably 20 parts by mass or less, and even more preferably 10 parts by mass or less, per 100 parts by mass of the (meth)acrylic copolymer (A).

[0053] The pressure-sensitive adhesive sheet of the present invention may contain a thermal crosslinking agent as necessary, but in terms of being particularly excellent in step conformability, the pressure-sensitive adhesive sheet of the present invention preferably contains a small amount of thermal crosslinking agent, and particularly preferably does not contain any thermal crosslinking agent. Therefore, the pressure-sensitive adhesive sheet of the present invention preferably contains 1 part by mass or less of thermal crosslinking agent relative to 100 parts by mass of (meth)acrylic copolymer (A), more preferably 0.1 parts by mass or less, and particularly preferably 0 parts by mass or less. The thermal curing agent referred to here means a material that can be cured by heat, and means known thermal crosslinking agents such as isocyanate compounds, epoxy compounds, oxazoline compounds, aziridine compounds, metal chelate compounds, and butylated melamine compounds.

[0054] The pressure-sensitive adhesive sheet of the present invention may contain additives that can be used as additives for pressure-sensitive adhesive sheets, as necessary, such as sensitizers, plasticizers, antioxidants, metal corrosion inhibitors, tackifiers, silane coupling agents, ultraviolet absorbers, light stabilizers, etc. As described above, when the pressure-sensitive adhesive sheet contains a self-cleavage type photoradical initiator (D) having an absorption wavelength peak of less than 340 nm, it is preferable to use an appropriate sensitizer.

[0055] The pressure-sensitive adhesive sheet of the present invention may be a single-sided pressure-sensitive adhesive sheet or a double-sided pressure-sensitive adhesive sheet. The pressure-sensitive adhesive sheet of the present invention may have a release sheet on one or both sides. The release sheet may be a release laminate sheet having a release sheet substrate and a release agent layer provided on one side of the release sheet substrate, or a polyolefin film such as a polyethylene film or a polypropylene film as a low-polarity substrate.

[0056] Paper or polymer film may be used as the substrate for the release sheet in the release laminate sheet. As the release agent constituting the release agent layer, for example, a general-purpose addition type or condensation type silicone-based release agent or a compound containing a long chain alkyl group is used. In particular, an addition type silicone-based release agent having high reactivity is preferably used. Specific examples of the silicone-based release agent include BY24-4527 and SD-7220 manufactured by Toray Dow Corning Silicone Co., Ltd., and KS-3600, KS-774, and X62-2600 manufactured by Shin-Etsu Chemical Co., Ltd. In addition, when SiO is contained in the silicone-based release agent, 2 Units and (CH 3 ) 3 SiO 1 / 2 Unit or CH 2 =CH(CH 3 )SiO 1 / 2 It is preferable that the silicone resin contains a silicone resin, which is an organosilicon compound having a unit. Specific examples of the silicone resin include BY24-843, SD-7292, SHR-1404, etc. manufactured by Dow Corning Toray Silicone Co., Ltd., and KS-3800, X92-183, etc. manufactured by Shin-Etsu Chemical Co., Ltd.

[0057] Commercially available peelable laminated sheets may be used, such as a heavy separator film made by Toyobo Co., Ltd., which is a release-treated polyethylene terephthalate film, and a light separator film made by Toyobo Co., Ltd., which is a release-treated polyethylene terephthalate film.

[0058] The pressure-sensitive adhesive sheet of the present invention preferably has a pair of release sheets with different peel strengths. If the releasability from one side differs from the other side, it becomes easy to first peel off only the release sheet with the stronger releasability.

[0059] The method for post-curing the pressure-sensitive adhesive sheet of the present invention is not particularly limited, and for example, a wide variety of known methods can be used. For example, the pressure-sensitive adhesive sheet can be post-cured by irradiating the laminate with active energy rays, as described below.

[0060] (Physical properties of adhesive sheet) The pressure-sensitive adhesive sheet of the present invention is a pressure-sensitive adhesive sheet represented by the following formula (1): R=S(LED) / S(HTML) (1) The value of R is 0.8 to 1.2.

[0061] S (HPML) is an adhesive sheet with an illuminance of 160mW / cm 2 The accumulated light intensity is 3000mJ / cm using a high-pressure mercury lamp. 2 After irradiating the sample with light, the sample was pulled at a speed of 300 mm / min until the tensile elongation reached 500%. The stress value [N / mm 2 S (LED) is a light source with an illuminance of 160mW / cm2 for adhesive sheets. 2 And an LED lamp with a wavelength of 365 nm is used, with an integrated light output of 3000 mJ / cm 2 After irradiating the sample with light, the sample was pulled at a speed of 300 mm / min until the tensile elongation reached 500%. The stress value [N / mm 2 ] is indicated.

[0062] S(HPML) is measured by the following procedure. An adhesive sheet with two release sheets with different peel strengths attached to both sides is cut to a length of 50 mm and a width (width direction) of A mm. In this case, the value of A in the width direction is calculated by the thickness of the adhesive sheet (mm) x A mm = 6 mm. 2 Then, the illuminance is set to 160 mW / cm 2 The accumulated light intensity is 3000mJ / cm using a high-pressure mercury lamp. 2 The adhesive sheet is then post-cured by irradiating it with light so that the adhesive sheet is in the state of being 2.8 mm in diameter and 50 mm in height. The release sheet with the lower peeling strength is then peeled off, and only the adhesive sheet is rolled in the width direction on the release sheet with the higher peeling strength to obtain a cylindrical sample with a diameter of 2.8 mm and a height of 50 mm. The cylindrical sample is sandwiched between two PET films (4 in total) with a thickness of 188 μm, a length of 25 mm, and a width of 50 mm, each of which is 10 mm from the top and bottom ends. After this, the area sandwiched between the two PET films is used as the chuck part of the tensile tester, and the chuck distance is fixed to 30 mm. After that, the sample is pulled until the tensile elongation reaches 500% at a tensile speed of 300 mm / min under an environment with a measurement temperature of 23°C and a relative humidity of 50%, and the stress value at this time is S(HPML).

[0063] S(LED) is measured using the following procedure. An adhesive sheet with two release sheets with different peel strengths attached to both sides is cut to a length of 50 mm and a width (width direction) of A mm. In this case, the value of A in the width direction is calculated by the thickness of the adhesive sheet (mm) x A mm = 6 mm. 2 Then, the illuminance is set to 160 mW / cm 2 and a 365 nm LED lamp with an integrated light output of 3000 mJ / cm 2The adhesive sheet is then post-cured by irradiating it with light so that the adhesive sheet is in the state of being 2.8 mm in diameter and 50 mm in height. The release sheet with the lower peeling strength is then peeled off, and only the adhesive sheet is rolled in the width direction on the release sheet with the higher peeling strength to obtain a cylindrical sample with a diameter of 2.8 mm and a height of 50 mm. The cylindrical sample is sandwiched between two PET films (4 in total) with a thickness of 188 μm, a length of 25 mm, and a width of 50 mm, each up to 10 mm from the top and bottom ends. After this, the area sandwiched between the two PET films is used as the chuck part of the tensile tester, and fixed so that the distance between the chucks is 30 mm. After that, the sample is pulled until the tensile elongation reaches 500% at a tensile speed of 300 mm / min under an environment with a measurement temperature of 23°C and a relative humidity of 50%, and the stress value at this time is S(LED).

[0064] If the value of R expressed by the formula (1) is outside the range of 0.8 to 1.2, the degree of cure of the adhesive sheet will vary greatly depending on the type of lamp used, resulting in problems with the stability of the product's performance. Therefore, by keeping the value of R expressed by the formula (1) within the range of 0.8 to 1.2, there will be no significant variation in the performance of the adhesive sheet after post-curing, regardless of whether the lamp used to irradiate the adhesive sheet is a high-pressure mercury lamp or an LED, so a stable product can be provided.

[0065] The value of R represented by the formula (1) is preferably 0.82 or more, more preferably 0.85 or more, and even more preferably 0.87 or more, and is preferably 1.1 or less, more preferably 1.05 or less, and even more preferably 1.0 or less. Both S(HPML) and S(LED) are preferably 0.05 N / mm 2 More preferably, 0.1N / mm 2 In this case, the pressure-sensitive adhesive sheet is unlikely to be insufficiently cured. In addition, both S(HPML) and S(LED) are preferably 0.4 N / mm 2 Less than or equal to 0.3N / mm 2 In this case, the pressure-sensitive adhesive sheet is unlikely to be excessively cured during post-curing, and therefore can have sufficient stress relaxation properties.

[0066] The pressure-sensitive adhesive sheet of the present invention exhibits excellent step conformability to the adherend even when the interval between steps on the adherend is narrow or the height or depth of the uneven shape constituting the steps is large. Furthermore, even if the pressure-sensitive adhesive sheet of the present invention is applied to the step portion and post-cured with active energy rays such as ultraviolet rays, and then exposed to ultraviolet rays, it is unlikely to deteriorate and the generation of bubbles and the like at the step portion is also suppressed.

[0067] Therefore, the pressure-sensitive adhesive sheet of the present invention is preferably a pressure-sensitive adhesive sheet for attachment to an adherend having at least one type selected from convex portions and concave portions. In particular, the pressure-sensitive adhesive sheet of the present invention is preferably a pressure-sensitive adhesive sheet for attachment to two adherends, specifically, for attachment to a first adherend having convex portions and a second adherend having at least one type selected from convex portions and concave portions.

[0068] The gel fraction (initial gel fraction) of the pressure-sensitive adhesive sheet of the present invention before post-curing is, for example, 5.0% or less, preferably 4.5% or less, more preferably 4.0% or less, even more preferably 3.5% or less, and particularly preferably 2.5% or less. The lower limit of the gel fraction of the pressure-sensitive adhesive sheet is not particularly limited, and may be, for example, 0%. By setting the gel fraction of the pressure-sensitive adhesive sheet before photocrosslinking within the above range, a pressure-sensitive adhesive sheet with excellent step conformability can be obtained.

[0069] The gel fraction of the adhesive sheet is a value measured by the following method. First, about 0.1 g of the adhesive sheet (adhesive layer only) is placed in a sample bottle, 30 ml of ethyl acetate is added, and the mixture is shaken for 24 hours. The contents of the sample bottle are then filtered through a 150 mesh stainless steel wire screen, and the residue on the screen is dried at 100°C for 1 hour to measure the dry weight W (g). The gel fraction is calculated from the obtained dry weight using the following formula: Gel fraction (%) = (dry mass W / collected mass of adhesive sheet) x 100 The value calculated from the above is the gel fraction (%).

[0070] The pressure-sensitive adhesive sheet of the present invention was placed under illumination of 160 mW / cm 2The accumulated light intensity is 3000mJ / cm using a high-pressure mercury lamp. 2 When the composition is post-cured by irradiating with light so as to obtain a gel fraction of, for example, 5% or more, more preferably 10% or more, and even more preferably 20% or more.

[0071] The pressure-sensitive adhesive sheet of the present invention was also tested at an illumination intensity of 160 mW / cm 2 And an LED lamp with a wavelength of 365 nm is used, with an integrated light output of 3000 mJ / cm 2 When the composition is post-cured by irradiating light so as to give a gel fraction of preferably 5% or more, more preferably 10% or more, and even more preferably 20% or more.

[0072] The thickness of the pressure-sensitive adhesive sheet of the present invention is not particularly limited and can be within an appropriate range depending on the purpose of use, and is, for example, preferably 5 to 500 μm, more preferably 30 to 300 μm, and even more preferably 50 to 200 μm. By setting the thickness of the pressure-sensitive adhesive sheet within the above range, the step-following ability and durability can be sufficiently improved.

[0073] 2. Manufacturing method of adhesive sheet The method for producing the pressure-sensitive adhesive sheet of the present invention is not particularly limited, and any known production method can be widely adopted as long as the sheet contains a specific component. For example, the pressure-sensitive adhesive sheet of the present invention can be produced by a method of coating a pressure-sensitive adhesive composition.

[0074] In this case, the components contained in the adhesive composition are the same as those contained in the above-mentioned adhesive sheet, and the content ratios thereof are also the same as those of the adhesive sheet. Therefore, the adhesive composition contains at least a (meth)acrylic copolymer (A), a crosslinking agent (B), a hydrogen abstraction type photoinitiator (C), and a self-cleavage type photoradical initiator (D), and the crosslinking agent (B) is contained in an amount of less than 5 parts by mass per 100 parts by mass of the (meth)acrylic copolymer (A), the hydrogen abstraction type photoinitiator (C) is contained in an amount of 0.3 parts by mass or less per 100 parts by mass of the (meth)acrylic copolymer (A), and the self-cleavage type photoradical initiator (D) is contained in an amount of 0.2 parts by mass or more per 100 parts by mass of the (meth)acrylic copolymer (A). The adhesive composition can be prepared, for example, by a known method.

[0075] The adhesive composition can be applied to a substrate to form a coating film to form an adhesive layer. The adhesive layer thus formed may be directly obtained as an adhesive sheet. The adhesive composition can be applied using a known coating device. Examples of the coating device include a blade coater, an air knife coater, a roll coater, a bar coater, a gravure coater, a microgravure coater, a rod blade coater, a lip coater, a die coater, and a curtain coater.

[0076] The thickness of the adhesive composition after coating is not particularly limited and can be appropriately set depending on the intended thickness of the adhesive layer. When the adhesive composition contains a solvent described below, the solvent can be removed by an appropriate method.

[0077] In order to improve the coating property of the adhesive composition, the adhesive composition may contain a solvent. Examples of the solvent include hydrocarbons such as hexane, heptane, octane, toluene, xylene, ethylbenzene, cyclohexane, and methylcyclohexane; halogenated hydrocarbons such as dichloromethane, trichloroethane, trichloroethylene, tetrachloroethylene, and dichloropropane; alcohols such as methanol, ethanol, propanol, isopropyl alcohol, butanol, isobutyl alcohol, and diacetone alcohol; ethers such as diethyl ether, diisopropyl ether, dioxane, and tetrahydrofuran; ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, isophorone, and cyclohexanone; esters such as methyl acetate, ethyl acetate, butyl acetate, isobutyl acetate, amyl acetate, and ethyl butyrate; polyols and derivatives thereof such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monomethyl ether acetate, propylene glycol monomethyl ether, propylene glycol monoethyl ether, and propylene glycol monomethyl ether acetate.

[0078] When the pressure-sensitive adhesive composition contains a solvent, the content ratio thereof is not particularly limited and can be, for example, within the same range as that of known pressure-sensitive adhesive compositions.

[0079] When applying the pressure-sensitive adhesive composition, the substrate to be used is not particularly limited.For example, the pressure-sensitive adhesive composition can be applied to various substrates such as a resin substrate and a glass substrate.When the substrate is the release sheet described above, the pressure-sensitive adhesive composition can be applied onto this release laminated sheet, or the pressure-sensitive adhesive composition can be applied directly onto the member to be bonded.

[0080] When the substrate is the release sheet, the above-mentioned pressure-sensitive adhesive sheet having a release sheet on one side can be obtained. In addition, by protecting the adhesive surface of the pressure-sensitive adhesive sheet having a release sheet on one side with a release sheet having the same or different releasability, a pressure-sensitive adhesive sheet having a release sheet on both sides can be obtained.

[0081] The adhesive sheet obtained as described above contains at least the (meth)acrylic copolymer (A), the crosslinking agent (B), the hydrogen abstraction type photoinitiator (C) and the self-cleavage type photoradical initiator (D), and is therefore in a so-called semi-cured state and has post-curing properties.

[0082] 3.Laminate The laminate of the present invention includes the pressure-sensitive adhesive sheet. For example, the laminate has a structure in which a first adherend, a pressure-sensitive adhesive sheet, and a second adherend are laminated in this order. In the laminate, the pressure-sensitive adhesive sheet is, for example, only a pressure-sensitive adhesive layer. The method of laminating the pressure-sensitive adhesive sheet to the adherend is not particularly limited, and for example, known methods such as roll lamination and vacuum lamination can be adopted.

[0083] In the laminate of the present invention, since the pressure-sensitive adhesive sheet has post-curing properties, for example, by irradiating with active energy rays, a curing reaction of the pressure-sensitive adhesive sheet (adhesive layer) proceeds, and the first adherend and the second adherend are firmly attached to the pressure-sensitive adhesive sheet. The method of irradiating with active energy rays is not particularly limited, and for example, a method similar to a known method can be widely adopted. In addition, the laminate can be irradiated with active energy rays from either the side of the first adherend or the side of the second adherend.

[0084] The first and second adherends may have at least one selected from a convex portion and a concave portion. In addition, the first and second adherends are preferably optical members. Examples of optical members include components of optical products such as touch panels and image display devices.

[0085] Examples of components of the touch panel include an ITO film in which an ITO film is provided on a transparent resin film, ITO glass in which an ITO film is provided on the surface of a glass plate, a transparent conductive film in which a transparent resin film is coated with a conductive polymer, a hard coat film, a fingerprint-resistant film, etc. The first and second adherends are preferably an ITO film in which an ITO film is provided on a transparent resin film, an ITO glass in which an ITO film is provided on the surface of a glass plate, or a transparent conductive film in which a transparent resin film is coated with a conductive polymer.

[0086] Examples of components of image display devices include anti-reflection films, alignment films, polarizing films, retardation films, and brightness-enhancing films used in liquid crystal display devices. Materials used for these components include glass, polycarbonate, polyethylene terephthalate, polymethyl methacrylate, polyethylene naphthalate, cycloolefin polymer, triacetyl cellulose, polyimide, and cellulose acylate. Among these, it is preferable that the first adherend is a touch panel using glass, polycarbonate, or polymethyl methacrylate, and the second adherend is an image display device such as a polarizing plate or an organic EL display.

[0087] Examples of the active energy rays to be irradiated to the laminate include ultraviolet rays, electron beams, visible light, X-rays, ion beams, etc., and among these, from the viewpoint of versatility, ultraviolet rays or electron beams are preferred, and ultraviolet rays are particularly preferred. Examples of the light source of ultraviolet rays that can be used include high-pressure mercury lamps, low-pressure mercury lamps, ultra-high-pressure mercury lamps, metal halide lamps, carbon arcs, xenon arcs, and electrodeless ultraviolet lamps.

[0088] In particular, since the pressure-sensitive adhesive sheet of the present invention contains a specified amount of the self-cleavage type photoradical initiator (D), it has high reactivity even when an LED lamp (eg, 365 nm) is used, and post-curing in the laminate tends to proceed.

[0089] Therefore, for the laminate including the pressure-sensitive adhesive sheet of the present invention, in addition to the conventional high pressure mercury or metal halide UV lamps, LED lamps can also be used, making it easy to manufacture the laminate and reducing the introduction cost. That is, the laminate including the pressure-sensitive adhesive sheet of the present invention can have stable performance regardless of the type of lamp used for post-curing.

[0090] Furthermore, because the content of these initiators is adjusted within an appropriate range, even if the adhesive sheet is exposed to ultraviolet light for a longer period of time after post-curing, excessive reaction of the hydrogen abstraction initiator is suppressed and the adhesive sheet does not become too hard, thereby significantly suppressing a decrease in stress relaxation properties and the generation of air bubbles. EXAMPLES

[0091] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the embodiments of these examples.

[0092] Example 1 A pressure-sensitive adhesive composition was prepared according to the formulation shown in Table 1. Specifically, the pressure-sensitive adhesive composition was prepared by mixing 100 parts by mass of "OP-9200-3" (ethyl acetate solution with a solid content of 40% by mass) manufactured by AICA Co., Ltd. as the (meth)acrylic copolymer (A), 3 parts by mass of propoxylated pentaerythritol tri- and tetraacrylate (ATM-4PL manufactured by Shin-Nakamura Chemical Co., Ltd.) as the crosslinking agent (B), 0.2 parts by mass of 4-methylbenzophenone ("SPEED CURE MBP" manufactured by LAMBSON, hereinafter referred to as "4MBP") as the hydrogen abstraction type photoinitiator (C), and 0.5 parts by mass of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide ("Omnirad TPO H" manufactured by IGM RESINS BV) as the self-cleavage type photoradical initiator (D).

[0093] This adhesive composition was uniformly applied with an applicator to the surface of a 38 μm-thick polyethylene terephthalate film (first release sheet) (Oji F-Tex Co., Ltd.: 38RL-07(2)) with a release layer treated with a silicone-based release agent, so that the coating thickness after drying would be 150 μm. Thereafter, it was dried for 10 minutes in an air-circulating thermostatic oven at 100° C. to form an adhesive layer on the surface of the first release sheet. Next, a 38 μm-thick second release sheet (Oji F-Tex Co., Ltd.: 38RL-07(L)) was attached to the surface of this adhesive layer to obtain a double-sided adhesive sheet with a release sheet having a configuration of first release sheet / adhesive layer / second release sheet, in which the adhesive layer is sandwiched between a pair of release sheets with a difference in release strength.

[0094] Example 2 A double-sided pressure-sensitive adhesive sheet with a release sheet was obtained in the same manner as in Example 1, except that the amounts of the (meth)acrylic copolymer (A), crosslinking agent (B), hydrogen abstraction type photoinitiator (C), and self-cleavage type photoradical initiator (D) used were changed as shown in Table 1.

[0095] Example 3 A double-sided pressure-sensitive adhesive sheet with a release sheet was obtained in the same manner as in Example 1, except that the crosslinking agent (B) was changed to "Viscoat #230" manufactured by Osaka Organic Chemical Industry Co., Ltd. and the amounts of the (meth)acrylic copolymer (A), crosslinking agent (B), hydrogen abstraction type photoinitiator (C), and self-cleavage type photoradical initiator (D) used were changed as shown in Table 1.

[0096] Example 4 A double-sided pressure-sensitive adhesive sheet with a release sheet was obtained in the same manner as in Example 1, except that the amounts of the (meth)acrylic copolymer (A), crosslinking agent (B), hydrogen abstraction type photoinitiator (C), and self-cleavage type photoradical initiator (D) used were changed as shown in Table 1.

[0097] Example 5 A double-sided adhesive sheet with a release sheet was obtained in the same manner as in Example 1, except that 5 parts by mass of "MEDOL-10" manufactured by Osaka Organic Chemical Industry Co., Ltd. was used as a monofunctional monomer and the amounts of the (meth)acrylic copolymer (A), crosslinking agent (B), hydrogen abstraction type photoinitiator (C), and self-cleavage type photoradical initiator (D) used were changed as shown in Table 1.

[0098] Example 6 A double-sided adhesive sheet with a release sheet was obtained in the same manner as in Example 1, except that the self-cleavage type photoradical initiator (D) was changed to "Omnirad184" manufactured by IGM RESINS BV, 0.1 parts by mass of "UVS-2171" manufactured by Kawasaki Chemical Industries, Ltd. was used in combination as a sensitizer, and the amounts of the (meth)acrylic copolymer (A), crosslinking agent (B), hydrogen abstraction type photoinitiator (C), and self-cleavage type photoradical initiator (D) used were changed as shown in Table 1.

[0099] Example 7 A double-sided pressure-sensitive adhesive sheet with a release sheet was obtained in the same manner as in Example 1, except that the amounts of the (meth)acrylic copolymer (A), crosslinking agent (B), hydrogen abstraction type photoinitiator (C), and self-cleavage type photoradical initiator (D) used were changed as shown in Table 1.

[0100] Example 8 A double-sided pressure-sensitive adhesive sheet with a release sheet was obtained in the same manner as in Example 1, except that the amounts of the (meth)acrylic copolymer (A), crosslinking agent (B), hydrogen abstraction type photoinitiator (C), and self-cleavage type photoradical initiator (D) used were changed as shown in Table 1.

[0101] Comparative Example 1 A double-sided pressure-sensitive adhesive sheet with a release sheet was obtained in the same manner as in Example 1, except that the amounts of the (meth)acrylic copolymer (A), crosslinking agent (B), hydrogen abstraction type photoinitiator (C), and self-cleavage type photoradical initiator (D) used were changed as shown in Table 1.

[0102] Comparative Example 2 A peelable - sheet - attached double - sided adhesive sheet was obtained in the same manner as in Example 1, except that the usage amounts of the (meth)acrylic copolymer (A), cross - linking agent (B), hydrogen - abstraction type photoinitiator (C), and self - cleavage type photo - radical initiator (D) were changed as shown in Table 1.

[0103] (Evaluation) <S(HPML); Tensile stress at 500% elongation> S(HPML) was measured as follows. First, the peelable - sheet - attached double - sided adhesive sheets obtained in the examples and comparative examples were cut out to a length of 50 mm and a width (in the width direction) of A mm. At this time, the value of A in the horizontal (width direction) was determined such that the thickness of the adhesive sheet (mm)×A mm = 6 mm. 2 Then, using a high - pressure mercury lamp with an illuminance of 160 mW / cm 2 the samples were post - cured by irradiating light so that the integrated light amount became 3000 mJ / cm 2 After that, the first peelable sheet was peeled off, and while rolling up only the adhesive sheet in the width direction, it was peeled off from above the second peelable sheet to obtain a cylindrical sample with a diameter of 2.8 mm and a height of 50 mm. The regions up to 10 mm from the upper and lower ends of the cylindrical sample were sandwiched between two PET films (a total of four films) with a thickness of 188 μm, a length of 25 mm, and a width of 50 mm. After this, the region sandwiched between the two PET films was used as the chuck part of a tensile testing machine and fixed so that the distance between the chucks was 30 mm. Then, under the conditions of a measurement temperature of 23°C and a relative humidity of 50%, it was pulled at a tensile speed of 300 mm / min until the tensile elongation rate reached 500%. The stress value at this time was defined as S(HPML).

[0104] <S(LED); Tensile stress at 500% elongation> The peelable - sheet - attached double - sided adhesive sheets obtained in the examples and comparative examples were newly cut out to a length of 50 mm and a width (in the width direction) of A mm separately from the measurement of S(HPML). At this time, the value of A in the horizontal (width direction) was determined such that the thickness of the adhesive sheet (mm)×A mm = 6 mm. 2 Then, using an LED lamp with an illuminance of 160 mW / cm 2 and a wavelength of 365 nm, the samples were irradiated with light so that the integrated light amount became 3000 mJ / cm 2The adhesive sheet was then post-cured by irradiating light so that the adhesive sheet was cured. The first release sheet was then peeled off, and the adhesive sheet alone was rolled in the width direction and peeled off from the second release sheet to obtain a cylindrical sample with a diameter of 2.8 mm and a height of 50 mm. The cylindrical sample was sandwiched between two PET films (4 in total) with a thickness of 188 μm, a length of 25 mm, and a width of 50 mm, each of which was up to 10 mm from the top and bottom ends. After this, the area sandwiched between the two PET films was used as the chuck part of the tensile tester, and the chuck distance was fixed to 30 mm. After that, the sample was pulled until the tensile elongation reached 500% at a tensile speed of 300 mm / min under an environment with a measurement temperature of 23°C and a relative humidity of 50%. The stress value at this time was taken as S(LED).

[0105] <Gel fraction (initial)> The adhesive sheet was peeled off from the double-sided adhesive sheet with release sheet obtained in the Examples and Comparative Examples, and about 0.1 g of the adhesive sheet (only the adhesive layer) was collected in a sample bottle, to which 30 ml of ethyl acetate was added and shaken for 24 hours. The contents of the sample bottle were then filtered through a 150 mesh stainless steel wire screen, and the residue on the wire screen was dried at 100°C for 1 hour to measure the dry weight W (g). The obtained dry weight was calculated using the following formula: Gel fraction (%) = (dry mass W / collected mass of adhesive sheet) x 100 The value calculated from the above was taken as the gel fraction (initial).

[0106] <Gel fraction (after post-curing)> In the measurement of S(HPML) described above, the gel fraction (after post-curing) was measured in the same manner as the gel fraction (initial), except that approximately 0.1 g of the post-cured pressure-sensitive adhesive sheet was placed in a sample bottle.

[0107] <Gel fraction (after UV exposure)> Using a Q-Lab QUV accelerated weathering tester, the adhesive sheet was tested at 60°C from the second release sheet side at 0.77 W m 2 The gel fraction (after UV exposure) was measured in the same manner as the gel fraction (initial), except that approximately 0.1 g of the adhesive sheet after 16 hours of UVA light irradiation was collected in a sample bottle.

[0108] <Evaluation of step conformability (after post-curing)> On the surface of a glass plate (length 90 mm × width 50 mm × thickness 0.5 mm), ultraviolet-curable ink was screen-printed in a frame shape (length 90 mm × width 50 mm, width 5 mm) so that the coating thickness was 5 μm. Next, the printed ultraviolet-curable ink was irradiated with ultraviolet light to cure. This process was repeated a predetermined number of times to obtain a printed stepped glass (first adherend) having a stepped portion with a thickness of 50 μm. Next, a second adherend was produced by the following procedure. First, a polarizing plate with an adhesive layer (polarizing plate manufactured by Samsung SDI: "2144") having a total thickness of 80 μm including the polarizing plate and the adhesive was cut into a length of 90 mm × width 50 mm. Next, a circular hole with a diameter of 4 mm was made at a position 15 mm from the top end and 10 mm from the left end, and then the glass plate was attached to another glass plate (length 90 mm × width 50 mm × thickness 0.5 mm) to obtain a glass plate with a perforated polarizing plate (second adherend).

[0109] Next, the double-sided adhesive sheet with release sheet obtained in the examples and comparative examples was cut into a shape of 90 mm long x 50 mm wide, the first release sheet was peeled off, and the adhesive sheet (adhesive layer) was attached to the entire surface of the first adherend using a laminator (IKO-650EMT, manufactured by Yubon Co., Ltd.). Thereafter, the second release sheet was peeled off, and the polarizing plate side of a glass plate with a perforated polarizing plate (90 mm long x 50 mm wide x 0.5 mm thick) was attached to the exposed adhesive sheet (adhesive layer) using a vacuum laminator (JE2020B-MVH, manufactured by Joyo Engineering Co., Ltd.). The lamination conditions at this time were 40°C, weak pressure of 0.6 kN, strong pressure of 1.2 kN, vacuum pressure of 100 Pa, and pressure retention time of 10 seconds. Next, a degassing treatment (autoclave treatment: 60°C, 0.5 MPa, 30 minutes) was performed. After that, the illuminance was 160mW / cm from the printed step glass side. 2 A high-pressure mercury lamp is used, with an integrated light output of 3000mJ / cm 2 The printed step portion of the laminate and the hole portion of the polarizing plate (collectively referred to as step portion) were observed under a microscope (magnification: 25 times) and evaluated according to the following criteria. ◯: No air bubbles were observed in the stepped portion, and the stepped portion was completely filled. ×: Air bubbles were observed in the stepped portion, and the stepped portion was not filled.

[0110] <Stress relaxation evaluation (after post-curing)> The laminate produced for the step conformability evaluation (after post-curing) was placed in a thermal shock tester and subjected to 100 cycles of 30 minutes at 80°C and 30 minutes at -40°C. The step portion of the laminate, mainly of the second adherend, was observed under a microscope (magnification: 25x) and evaluated according to the following criteria. ◯: No air bubbles were observed in the stepped portion, and the stepped portion was completely filled. ×: Air bubbles were observed in the stepped portion, and the stepped portion was not filled.

[0111] <Stress relaxation evaluation (after UV exposure)> The laminate produced for the step conformability evaluation (after post-curing) was placed in a QUV tester (Q-LAB), and 0.77 W / m was applied from the printed step glass side. 2 After irradiating with ultraviolet light (UV-A) at 60°C for 16 hours, the laminate was placed in a thermal shock tester and treated with 100 cycles of 30 minutes at 80°C and 30 minutes at -40°C. The laminate that had been subjected to the thermal shock test after exposure to ultraviolet light was observed mainly at the step portion of the second adherend with a microscope (magnification: 25x) and evaluated according to the following criteria. ◯: No air bubbles were observed in the stepped portion, and the stepped portion was completely filled. ×: Air bubbles were observed in the stepped portion, and the stepped portion was not filled.

[0112] <Quality variation> ◯: The R value was within the range of 0.8 to 1.2, and the pressure-sensitive adhesive sheet was capable of providing products with stable quality regardless of the type of lamp. ×: The R value was outside the range of 0.8 to 1.2, and the adhesive sheet caused quality variations depending on the type of lamp.

[0113] [Table 1]

[0114] Table 1 shows the synthesis conditions (types of components and their blending conditions) and evaluation results of the pressure-sensitive adhesive sheets of each Example and Comparative Example. In the table, the blending amount of each component is in parts by mass, and the gel fraction is in %.

[0115] The adhesive sheets obtained in the examples were blended with the prescribed amounts of each component, had a value of R=S(LED) / S(HTML) in the range of 0.8 to 1.2, and exhibited stable curing properties regardless of the type of lamp, excellent step conformability, and excellent stress relaxation properties. In particular, the stress relaxation properties were excellent even after exposure to ultraviolet light.

[0116] In contrast, in Comparative Example 1, the amount of crosslinking agent (B) was too much, so the value of R did not fall within the specified range, which caused a large variation in the quality of the product cured with high pressure mercury and LED, and the stress relaxation property was also poor. In Comparative Example 2, the amount of hydrogen abstraction type photoinitiator (C) was too much, so the value of R fell within the specified range, but the gel fraction became too high after exposure to ultraviolet light, and a decrease in stress relaxation property was observed after exposure to ultraviolet light. In Comparative Example 3, the amount of hydrogen abstraction type photoinitiator (C) was not included, so the curing was insufficient, and bubbles were generated due to insufficient cohesion. In Comparative Example 4, the amount of abstraction type photoinitiator (C) was too much, so the gel fraction became too high after exposure to ultraviolet light, and a decrease in stress relaxation property was observed after exposure to ultraviolet light. In Comparative Example 5, the amount of self-cleavage type photoradical initiator (D) was too little, so the product was not cured sufficiently, causing a decrease in adhesion, and the value of R was also small, which caused a large variation in the quality of the product cured with high pressure mercury and LED.

Claims

1. A (meth)acrylic copolymer (A), A crosslinking agent (B) having two or more acryloyl groups; A hydrogen abstraction type photoinitiator (C); A self-cleavage type photoradical initiator (D); Including, The hydrogen abstraction type photoinitiator (C) is at least one selected from the group consisting of benzophenone, benzoylbenzoic acid, methyl benzoylbenzoate, 4-phenylbenzophenone, hydroxybenzophenone, 3,3'-dimethyl-4-methoxybenzophenone, 2,4,6-trimethylbenzophenone, 4-methylbenzophenone, thioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone, 2,4-dimethylthioxanthone, isopropylthioxanthone, camphorquinone, dibenzosuberone, 2-ethylanthraquinone, 3,3',4,4'-tetra(t-butylperoxycarbonyl)benzophenone, and 9,10-phenanthrenequinone; The self-cleavage type photoradical initiator (D) has an absorption wavelength peak in the wavelength range of 220 to 450 nm, The crosslinking agent (B) is contained in an amount of less than 5 parts by mass relative to 100 parts by mass of the (meth)acrylic copolymer (A), the hydrogen abstraction type photoinitiator (C) is contained in an amount of 0.3 parts by mass or less based on 100 parts by mass of the (meth)acrylic copolymer (A); The self-cleavage type photoradical initiator (D) is contained in an amount of 0.2 parts by mass or more per 100 parts by mass of the (meth)acrylic copolymer (A), The following formula (1) R=S(LED) / S(HTML) (1) (Here, S(HPML) is the illuminance of 160 mW / cm for the adhesive sheet. 2 A high-pressure mercury lamp was used with an integrated light intensity of 3000 mJ / cm 2 After irradiating the sample with light so as to obtain a stress value [N / mm 2 ], and S (LED) has an illuminance of 160 mW / cm 2 And an LED lamp with a wavelength of 365 nm is used to obtain an integrated light quantity of 3000 mJ / cm 2 After irradiating the sample with light so as to obtain a stress value [N / mm 2 ]) The pressure-sensitive adhesive sheet has an R value of 0.8 to 1.

2.

2. The pressure-sensitive adhesive sheet according to claim 1, wherein the (meth)acrylic copolymer (A) has a glass transition temperature of -50°C to -40°C and a mass average molecular weight of 250,000 to 450,000.

3. The pressure-sensitive adhesive sheet according to claim 1 , wherein the (meth)acrylic copolymer (A) does not contain an acryloyl group in its structural unit.

4. The pressure-sensitive adhesive sheet according to any one of claims 1 to 3, which does not contain a thermal crosslinking agent.

5. A laminate comprising the pressure-sensitive adhesive sheet according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • Pressure-sensitive adhesive sheet

    JP2009292986A

  • Pressure-sensitive adhesive composition, pressure-sensitive adhesive and pressure-sensitive adhesive sheet

    JP2013203899A

  • Adhesive composition, optical member and adhesive sheet

    JP2016035046A

  • Curable compositions for pressure-sensitive adhesives

    US20210189042A1